(untitled) (The Eurasia Proceedings of Educational and Social Sciences, 2019)
This paper investigates to what extetnt the Early Childhood Education (ECE) initial teachers education preperation program at the Lebanese University Faculty of Education, develop pre-service teachers’ Pedagogical Content Knowlede competences (PCK) to teach science for early years. For this purpose, an original analysis framework was developed by the researchers after extensive review of the existing literature and theories covering science education for early childhood education teaching program. To assess the development of science education PCK competences over the three years of the program, a questionnaire, developed and validated by the researchers, was completed by 56 graduate ECE pre-service teachers, measuring the content knowledge. In addition, content analysis of the science lesson plans completed by the pre-service teachers during their training sessions and retreived from their portfolios, associated with an interview with their trainers. The findings show that competences related to content knowledge are not developed, whereas the development of other competences varies between not and fairly developed.